2010
DOI: 10.4014/jmb.0909.09041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Expression of Genes in the Sphingolipid Synthesis Pathway on the Biosynthesis of Ceramide in Saccharomyces cerevisiae

Abstract: Ceramide is important not only for the maintenance of the barrier function of the skin but also for the waterbinding capacity of the stratum corneum. Although the exact role of ceramide in the human skin is not fully understood, ceramide has become a widely used ingredient in cosmetic and pharmaceutical industries. Compared with other microorganisms, yeast is more suitable for the production of ceramide because yeast grows fast and is non-toxic. However, production of ceramide from yeast has not been widely st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…S10C). As an essential gene, YBR265W encodes 3-ketosphinganine reductase (Tsc10p) that catalyzes the second step in the pathway for sphingolipid synthesis in S. cerevisiae (25). Sphingolipids are reportedly involved in the regulation of the yeast high-osmolarity glycerol (HOG) response pathway (26).…”
Section: Resultsmentioning
confidence: 99%
“…S10C). As an essential gene, YBR265W encodes 3-ketosphinganine reductase (Tsc10p) that catalyzes the second step in the pathway for sphingolipid synthesis in S. cerevisiae (25). Sphingolipids are reportedly involved in the regulation of the yeast high-osmolarity glycerol (HOG) response pathway (26).…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we investigated whether Nvj2p allows cells to tolerate elevated ceramide synthesis and prevents ceramide accumulation. It has been found that overexpression of the ceramide synthase Lag1p increases ceramide levels and decreases growth rate (Kim et al, 2010). We introduced into wild-type cells a plasmid expressing Lag1p under the galactose-inducible GAL1 promoter.…”
Section: Nvj2p Prevents the Toxic Accumulation Of Ceramidesmentioning
confidence: 99%
“…Among all sphingolipid biosynthetic enzymes, Tsc10 localizes specifically to LDs with no functional implication (Currie et al, 2014). Tsc10 overexpression increases LCB and ceramide levels (Kim et al, 2010), whereas TSC10-DAmP mutant accumulated Figure 7. Blocking sphingolipid synthesis does not affect LD biogenesis, but LD morphology is affected by sphingoid intermediates.…”
Section: Sphingolipid Inhibitors Modulate the Interactions Of Seipin With Spt And Fa Elongasementioning
confidence: 99%